2017
DOI: 10.1016/j.jhazmat.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved organic matter derived from forest leaf litter on biodegradation of phenanthrene in aqueous phase

Abstract: Dissolved organic matter (DOM) released from forest leaf litter is potentially effective for the degradation of polycyclic aromatic hydrocarbons (PAHs), yet the inherent mechanism remains insufficiently elucidated. In this study, we investigated the effects of DOM derived from Pinus elliottii and Schima superba leaf litter on the degradation of phenanthrene by the phenanthrene degrading bacterium Sphingobium sp. Phe-1. DOM from different origins and at a large range of concentrations enhanced the degradation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…18 Lin et al 19 found that DOM promoted the bioavailability of pyrene when the freely dissolved concentration of pyrene was kept constant. Also, as suggested by Cai et al, 20 DOM enhanced the bioavailability of phenanthrene by facilitating the microbial accessed to DOMphenanthrene complex. The enhancement of polyferric aluminum sulfate (PFAS) bioaccumulation by Daphnia magna aer addition of DOM at a low level was also found by Xia et al 21 Therefore, DOM is a key component of the global carbon cycle and it is considered as the most active chemical group in terrestrial and aquatic ecosystems with its contribution of natural ligands and adsorption carriers in the environment.…”
Section: Introductionmentioning
confidence: 82%
“…18 Lin et al 19 found that DOM promoted the bioavailability of pyrene when the freely dissolved concentration of pyrene was kept constant. Also, as suggested by Cai et al, 20 DOM enhanced the bioavailability of phenanthrene by facilitating the microbial accessed to DOMphenanthrene complex. The enhancement of polyferric aluminum sulfate (PFAS) bioaccumulation by Daphnia magna aer addition of DOM at a low level was also found by Xia et al 21 Therefore, DOM is a key component of the global carbon cycle and it is considered as the most active chemical group in terrestrial and aquatic ecosystems with its contribution of natural ligands and adsorption carriers in the environment.…”
Section: Introductionmentioning
confidence: 82%
“…Some studies, however, reported that DOM enhanced microbial degradation of HOCs, not only by stimulating microbial growth as a carbon source or microbial nutrient , but also by adjusting bacteria cell wall properties for internalizing HOCs, which eventually increased the bioactivity of the degrading strain. Another study documented that in a PHE degradation system where HA was present HA was cometabolized by the degrading bacteria during the PHE biodegradation process …”
Section: Resultsmentioning
confidence: 99%
“…comm., compared to Thailand mangroves: 1.4–1.7 mmol m −2 h −1 ; Poungparn et al 2012). Overall, it appears that high production of biomass OC would ultimately enrich DOM concentration in the pore water and swamp surface water by active leaching of plant‐derived organic acids (Cai et al 2017).…”
Section: Discussionmentioning
confidence: 99%